The impact of maximized resection and standardized systemic therapy on overall survival in adult patients with thalamic gliomas - Wang, Junjie; Niu, Xiaodong; Chang, Tao; Quan, Yuxin; Mwibwe, Lloyd Mulenga; Liu, Yanhui; Wang, Xiang; Yang, Yuan; Mao, Qing (Frontiers in Oncology, 2025)
ObjectiveThis study aims to explore the impact of maximized resection and standardized systemic surgery + chemoradiotherapy(SRC) on the survival prognosis of adult thalamic glioma, and to construct a clinical prognosis model of adult thalamic glioma.MethodsA retrospective analysis was conducted on adult cases of thalamic glioma who underwent craniotomy in the Department of Neurosurgery of West China Hospital of Sichuan University from 01/03/2009 to 01/03/2024. Firstly, Kaplan-Meier survival analysis and subgroup analysis were conducted. Secondly, COX regression and LASSO-COX regression were performed on 12 variables respectively to screen the variables and construct a prognostic model. Then, the efficacy of different models was compared to select the optimal model to construct a prognostic nomogram for the overall survival of thalamic glioma.ResultsTotal of 192 adult patients with thalamic glioma were included in this study, of whom 84 underwent surgery only, 41 underwent surgery + radiotherapy/chemotherapy(SR/SC), and 67 completed SRC. Among them, 79 patients(41.1%) completed gross-total tumor resection during the operation, and 113 patients(58.9%) completed non-gross-total tumor resection. The efficacy of the three models was compared. The optimal LASSO-COX model included five variables that affected the overall survival(OS) of thalamic glioma (EOR, diagnosis, preoperative hydrocephalus, postoperative KPS, treatment). Then, these five variables were utilized to develop prognostic nomograms for predicting the 6-, 12-, 24-, 36-, and 60-month OS. The nomogram shows good predictive ability and clinical practicability. Finally, the risk stratification system based on the prognostic nomogram effectively divided patients into the high-risk group and the low-risk group.ConclusionsMaximized tumor resection within safe parameters with standardized systemic SRC significantly prolong the OS of patients with thalamic glioma. The survival prognosis nomogram based on LASSO-COX regression in this study can be used as a practical tool for predicting the survival probability of patients with thalamic glioma.